IDENTIFICATION OF FISHING GROUND FOR DEEP SEA DEMERSAL FISHES AND IT'S POSSIBILITY FOR FISHING DEVELOPMENT IN THE INDIAN OCEAN - Wudianto Wudianto; Fayakun Satria (Indonesian Fisheries Research Journal, 2007)
The topographical surveys were conducted from September 1st to 20th 2004 at southern part of Java and from September 20th to October 30th 2004 at the western part of Sumatera. Exact isobaths were necessary to determine the size of the area in order to identify the possible fishing ground for deep sea demersal fishes.